Applying a social-ecological model to understand factors impacting demand for childhood vaccinations in Nigeria, Uganda, and Guinea - James Bell; Belinda Lartey; Gemma Spickernell; Natasha Darrell; Frances Salt; Cassie Gardner; Emily Richards; Lanre Fasakin; Shadrach Egbeniyi; Emmanuel Odongo; James Ssenkungu; Rigobert Kotchi Kouadio; et al. (Elsevier, 2022)
Vaccines have reduced child mortality across the world, but low levels of demand for vaccination threatens to undermine progress. Existing frameworks to understand demand tend to prioritise primary caregivers' decision-making processes. We aimed to build a wider understanding of vaccine demand by applying an adapted socio-ecological model to analyse 158 interviews with primary caregivers and fathers of young children, and community influencers in Nigeria, Uganda, and Guinea. We found that several factors come together to inform a primary caregiver's demand for vaccination, including their familial and social relationships, their interactions with government and healthcare institutions, and the wider social and cultural norms in their communities. The study suggests that interventions targeted at families and communities instead of individuals could be effective. The results could be used to ensure that vaccine demand frameworks used by researchers and intervention designers are comprehensive and consider a wider range of influences on the primary caregiver.